Arterial hypertension in the family: the need for family care - Lopes, Mislaine Casagrande de Lima; Marcon, Sonia Silva (Revista da Escola de Enfermagem da USP, 2009)
This qualitative study was performed from March to July 2007 in the city of Maringá, Paraná State, Brazil, and aimed to understand the family's experience with arterial hypertension (AH), using Grounded Theory as the methodological framework. Informants were 14 families that live with different AH stages. The data were obtained through open interviews. The results showed that family participation is an important factor for disease treatment and control, and that this action is differentiated when individuals present some sort of dependence. If dependence occurs, there is caregiver overload; when dependence does not exist, family participation is sporadic, being limited to helping the patients in the drug treatment and accompanying them to the medical appointment. In some cases, other family members present habit changes relating to food and practicing physical activities. The results reinforce the need for family-centered hypertensive patient care.